Composite oxide-based gas sensitive material and sensor, method and use

CN122814699APending Publication Date: 2026-09-25XI AN JIAOTONG UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611320332.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-09-25

AI Technical Summary

Technical Problem

已有相关研究将ZIF衍生的ZnO基复合材料用于气体传感,但主要集中在醇类、NO2或H2S等气体的检测,对于乙炔这一特定目标气体的选择性敏感研究仍较欠缺

Benefits of technology

[0017](1)本发明提供一种的复合氧化物基体气体敏感材料,以双金属ZnCo-ZIF为前驱体,煅烧后ZnO与Co3O4两相形成高密度p-n异质结,结合高度分散的贵金属纳米颗粒,为乙炔分子的吸附和反应提供了丰富的活性位点与快速的扩散通道。基于所述气体敏感材料的传感器,器件结构成熟、制备稳定性好,对乙炔具有检测下限低、线性度好、重复性优异和选择性良好的气敏性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122814699A_ABST
    Figure CN122814699A_ABST
Patent Text Reader

Abstract

The application discloses a composite oxide-based gas sensitive material and a sensor, a method and application. The gas sensitive material comprises: a porous zinc-cobalt composite oxide base; and noble metal nanoparticles loaded on the porous zinc-cobalt composite oxide base. The application realizes high dispersion and strong interface combination of the noble metal nanoparticles in the base by in-situ introduction of a bimetallic organic framework precursor and reduction of the noble metal, effectively inhibits aggregation of an active component, and improves sensitivity, selectivity and stability of the sensor to acetylene. The preparation process is simple and easy for batch production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of semiconductor metal oxide gas sensor technology, specifically relating to a composite oxide matrix gas sensitive material, sensor, method, and application. Background Technology

[0002] Metal oxide semiconductor gas sensors have been widely studied in the field of toxic, harmful, flammable, and explosive gas detection due to their advantages such as simple structure, low cost, and ease of integration. ZnO, as a typical n-type wide-bandgap semiconductor, possesses good chemical stability and gas-sensing activity, and is commonly used for the detection of various reducing gases. However, the sensitivity of ZnO material alone to acetylene is relatively low, typically only showing a significant response at concentrations above 100 ppm. Furthermore, at operating temperatures, it is easily affected by cross-interference from coexisting reducing gases such as H2, CO, and CH4, resulting in insufficient selectivity and making it difficult to meet the requirements for accurate identification of low concentrations of acetylene in practical working conditions.

[0003] To improve the performance of ZnO-based gas-sensitive materials, researchers have attempted to enhance their responsiveness and selectivity by constructing composite oxide heterostructures or introducing noble metal catalytic components. On one hand, forming a heterojunction by combining ZnO with p-type Co3O4, utilizing the interfacial barrier modulation effect and synergistic catalysis, holds promise for improving the gas-sensitive response to acetylene. On the other hand, the catalytic sensitization effect of noble metals such as Pt can effectively reduce the reaction activation energy, promoting the chemical reaction of target gas molecules on the material surface, thereby improving sensitivity and selectivity. However, existing methods often employ co-precipitation, hydrothermal, or sol-gel routes for the preparation of composite oxides. These routes often suffer from uneven distribution of Zn and Co elements, random heterojunction interfaces, and low specific surface areas, making it difficult to form stable and controllable sensitive structures. Furthermore, the introduction of noble metal Pt typically involves impregnation or deposition onto the surface of synthesized oxides, which easily leads to Pt particle agglomeration, poor dispersion, and poor metal-oxide interface consistency, thus affecting the sensor's response value, response-recovery speed, and batch-to-batch repeatability.

[0004] Studies have shown that metal-organic frameworks (MOFs), acting as self-sacrificing templates, can derive metal oxides with high specific surface areas and regular porous structures after calcination. Furthermore, the two metal elements in bimetallic MOFs exhibit atomic-level uniform distribution at the framework nodes, providing a feasible pathway for preparing composite oxides with homogeneous composition. Previous research has utilized ZnO-based composites derived from ZIFs for gas sensing, but this has primarily focused on the detection of gases such as alcohols, NO2, or H2S. Research on the selective sensitivity for acetylene, a specific target gas, remains insufficient. Simultaneously, a mature technical solution has yet to be found for achieving highly dispersed Pt component introduction during the MOF precursor stage and forming a stable catalytic interface with the bimetallic oxide matrix.

[0005] Furthermore, the consistency of the sensitive layer coating and the long-term operational stability of existing acetylene sensors in the side-heated ceramic tube device structure still need improvement, especially in terms of low-concentration detection limits and repeatability, which restricts the practical application and promotion of this type of sensor.

[0006] For the reasons mentioned above, there is an urgent need to develop an acetylene sensor and its preparation method that can achieve uniform distribution of sensitive components and efficient dispersion of precious metals, and has high sensitivity and excellent selectivity for low concentrations of acetylene, so as to overcome the defects of existing technologies such as low response value, insufficient anti-interference ability and poor stability of preparation process. Summary of the Invention

[0007] To overcome the above problems, this invention proposes a composite oxide-based gas-sensitive material, sensor, method, and application. This invention achieves high dispersion and strong interfacial bonding of noble metal nanoparticles in the matrix by in-situ introduction of a bimetallic organic framework precursor, followed by reduction and calcination. This effectively inhibits the aggregation of active components, improves the sensor's sensitivity, selectivity, and stability to acetylene, and the preparation process is simple and easy for mass production.

[0008] Specifically, the object of the present invention is to provide the following aspects:

[0009] In a first aspect, a composite oxide-based gas-sensitive material is provided, the gas-sensitive material comprising: a porous zinc-cobalt composite oxide matrix and noble metal nanoparticles; wherein the noble metal nanoparticles are loaded on the porous zinc-cobalt composite oxide matrix.

[0010] In a second aspect, a method for preparing the composite oxide-based gas-sensitive material described in the first aspect is provided, the method comprising:

[0011] Step 1: Prepare a bimetallic organic framework precursor containing zinc and cobalt;

[0012] Step 2: Introduce a noble metal precursor into the bimetallic organic framework precursor and perform a reduction treatment to obtain a noble metal modified composite material.

[0013] Step 3: Calcine the precious metal-modified composite material to obtain the gas-sensitive material.

[0014] Thirdly, the application of the composite oxide-based gas-sensitive material according to the first aspect or the composite oxide-based gas-sensitive material prepared according to the method of the second aspect in sensors is provided.

[0015] Fourthly, an acetylene sensor is provided, the sensor comprising a sensitive layer containing the composite oxide matrix gas sensitive material described in the first aspect.

[0016] The beneficial effects of this invention include:

[0017] (1) This invention provides a composite oxide-based gas-sensitive material, using a bimetallic ZnCo-ZIF as a precursor. After calcination, ZnO and Co3O4 form a high-density pn heterojunction, which, combined with highly dispersed noble metal nanoparticles, provides abundant active sites and rapid diffusion channels for the adsorption and reaction of acetylene molecules. The sensor based on this gas-sensitive material has a mature device structure, good fabrication stability, and exhibits low detection limit, good linearity, excellent repeatability, and good selectivity for acetylene.

[0018] (2) In this invention, a noble metal precursor is introduced into the ZnCo-ZIF precursor stage and reduced, and then calcined to form a gas sensor. By utilizing the channel confinement effect of the ZIF framework and the uniform distribution of metal nodes, the noble metal component is highly dispersed and loaded in the composite oxide, effectively avoiding the agglomeration of noble metals. At the same time, the preparation route of ZIF template derivation combined with ceramic tube coating is adopted, which does not rely on complex processes such as MEMS micromachining. It is simple to operate, has mild conditions, is suitable for mass production, and has high industrial application prospects. Attached Figure Description

[0019] Various other advantages and benefits of the present invention will become apparent to those skilled in the art upon reading the detailed description of the preferred embodiments below. The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. It is obvious that the drawings described below are merely some embodiments of the invention, and those skilled in the art can obtain other drawings based on these drawings without any inventive effort.

[0020] In the attached diagram:

[0021] Figure 1 A schematic diagram of the acetylene sensor structure of the present invention is shown;

[0022] Figure 2 (a) shows a scanning electron microscope image of the gas-sensitive material prepared in Example 1;

[0023] Figure 2 (b) shows a high-magnification scanning electron microscope image of the gas-sensitive material prepared in Example 1;

[0024] Figure 3 The image shows a high-angle annular dark-field scanning transmission electron microscope image of the gas-sensitive material prepared in Example 1 and an elemental distribution map of Pt, Zn, Co, and O.

[0025] Figure 4The X-ray diffraction pattern of the gas-sensitive material prepared in Example 1 is shown;

[0026] Figure 5 The adsorption-desorption curves of the gas-sensitive material prepared in Example 1 are shown.

[0027] Figure 6 The pore size distribution of the gas-sensitive material prepared in Example 1 is shown;

[0028] Figure 7 (a) shows a scanning electron microscope image of the gas-sensitive material prepared in Example 2;

[0029] Figure 7 (b) shows a high-magnification scanning electron microscope image of the gas-sensitive material prepared in Example 2;

[0030] Figure 8 The image shows a high-angle annular dark-field scanning transmission electron microscope image of the gas-sensitive material prepared in Example 2 and an elemental distribution diagram of Pt, Zn, Co, and O.

[0031] Figure 9 The X-ray diffraction pattern of the gas-sensitive material prepared in Example 2 is shown;

[0032] Figure 10 The adsorption-desorption curves of the gas-sensitive material prepared in Example 2 are shown.

[0033] Figure 11 The pore size distribution of the gas-sensitive material prepared in Example 2 is shown;

[0034] Figure 12 (a) shows a scanning electron microscope image of the gas-sensitive material prepared in Example 3;

[0035] Figure 12 (b) shows a high-magnification scanning electron microscope image of the gas-sensitive material prepared in Example 3;

[0036] Figure 13 The image shows a high-angle annular dark-field scanning transmission electron microscope image of the gas-sensitive material prepared in Example 3 and an elemental distribution map of Pt, Zn, Co, and O.

[0037] Figure 14 The X-ray diffraction pattern of the gas-sensitive material prepared in Example 3 is shown;

[0038] Figure 15 The adsorption-desorption curves of the gas-sensitive material prepared in Example 3 are shown.

[0039] Figure 16 The pore size distribution of the gas-sensitive material prepared in Example 3 is shown;

[0040] Figure 17 Figure (a) shows the response curve of the sensor prepared in Example 4 to 100 ppm acetylene as a function of temperature;

[0041] Figure 17 Figure (b) shows the dynamic response curve of the sensor to a concentration gradient of 20-160 ppm acetylene at 240°C, prepared in Example 4;

[0042] Figure 17 (c) shows the linear response fitting curve of the sensor prepared in Example 4 in the range of 20 to 80 ppm;

[0043] Figure 17 (d) shows the response / recovery time curves of the sensor prepared in Example 4 at different acetylene concentrations;

[0044] Figure 17 (e) shows the response curve of the sensor prepared in Example 4 to 100 ppm acetylene in a 5-cycle test;

[0045] Figure 17 Figure (f) shows the selective response of the sensor prepared in Example 4 to acetylene and common interfering gases. Detailed Implementation

[0046] Specific embodiments of the invention will now be described in more detail with reference to the accompanying drawings. While specific embodiments of the invention are shown in the drawings, it should be understood that the invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided to enable a more thorough understanding of the invention and to fully convey the scope of the invention to those skilled in the art.

[0047] It should be noted that certain terms are used in the specification and claims to refer to specific components. Those skilled in the art will understand that different terms may be used to refer to the same component. This specification and claims do not distinguish components based on differences in terminology, but rather on differences in function. The terms "comprising" or "including" used throughout the specification and claims are open-ended and should be interpreted as "comprising but not limited to." The following descriptions are preferred embodiments for carrying out the invention; however, these descriptions are for the purpose of understanding the general principles of the specification and are not intended to limit the scope of the invention. The scope of protection of this invention is determined by the appended claims.

[0048] In the description of this invention, it should be noted that the terms "upper," "lower," "inner," "outer," "front," and "rear," etc., indicate the orientation or positional relationship based on the orientation or positional relationship in the working state of this invention, and are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this invention. Furthermore, the terms "first," "second," "third," and "fourth" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.

[0049] To facilitate understanding of the embodiments of the present invention, further explanations and descriptions will be provided below with reference to the accompanying drawings and specific embodiments. The accompanying drawings do not constitute a limitation on the embodiments of the present invention.

[0050] On one hand, according to the present invention, a composite oxide matrix gas-sensitive material comprises: a porous zinc-cobalt composite oxide matrix and noble metal nanoparticles; wherein the noble metal nanoparticles are loaded on the porous zinc-cobalt composite oxide matrix.

[0051] In this invention, a porous zinc-cobalt composite oxide matrix is ​​used as a carrier. The porous structure refers to the pore structure formed after the organic ligands are removed by calcination of the ZIF precursor. The abundant pore structure of the porous zinc-cobalt composite oxide matrix provides highly dispersed anchoring points for noble metal nanoparticles. At the same time, the noble metal nanoparticles loaded on the matrix can form a heterojunction interface with the zinc-cobalt oxide, promoting electron transport and oxygen species activation, thereby enhancing the gas-sensitive response capability to the target gas acetylene.

[0052] The porous zinc-cobalt composite oxide matrix comprises ZnO and Co3O4 crystal phases, and the porous zinc-cobalt composite oxide matrix consists of dodecahedral particles; the noble metal nanoparticles are platinum nanoparticles.

[0053] In this invention, by defining the matrix as a bicrystalline phase of ZnO and Co3O4, the width of the depletion layer is adjusted by utilizing the pn heterojunction formed between n-type ZnO and p-type Co3O4, which significantly improves the resistance change rate. The dodecahedral particles retain the template-derived porous structure, which is conducive to the rapid diffusion and adsorption of gas molecules. As a highly efficient catalytic active center, platinum nanoparticles can reduce the activation energy of the acetylene oxidation reaction, further improving the sensitivity and selectivity of the sensor.

[0054] The platinum nanoparticles have a particle size of 2-6 nm and a D50 of 4 nm. This invention controls the size of the platinum nanoparticles within the nanoscale range, which is beneficial for increasing the specific surface area of ​​platinum, providing sufficient catalytic active sites, and promoting the adsorption and dissociation of acetylene molecules on the platinum surface. If the platinum particle size is too large, its specific surface area decreases significantly, reducing the number of active sites provided per unit mass of platinum, thus lowering the catalytic efficiency. Furthermore, the number of interfaces between large platinum particles and the porous zinc-cobalt composite oxide matrix is ​​limited, weakening the electronic sensitization effect. If the platinum particle size is too small, the surface energy is too high, making it prone to agglomeration and growth during calcination or sensor operation, resulting in insufficient long-term stability.

[0055] In the porous zinc-cobalt composite oxide matrix, Zn and Co elements are uniformly distributed within the matrix. This uniform distribution originates from the Zn in the bimetallic ZnCo-ZIF precursor. 2+ and Co 2+ The uniform distribution of Zn and Co on the framework, after calcination to remove organic ligands, preserves this uniformity in the oxide product. This uniform distribution allows for the uniform intercalation of the ZnO and Co3O4 phases at the nanoscale, maximizing the interfacial density of the pn heterojunction. This enables the depletion layer modulation effect to be fully realized in the bulk phase, significantly improving the acetylene-induced resistivity change rate. Furthermore, the uniform elemental distribution avoids the baseline resistance drop and increased signal noise caused by localized Co segregation forming highly conductive regions, which is beneficial for lowering the sensor's detection limit and improving its long-term stability.

[0056] The specific surface area of ​​the porous zinc-cobalt composite oxide matrix is ​​15~30m². 2 / g. The porous structure provides ample sites for acetylene molecule adsorption and surface reactions, while ensuring the accessibility of gas molecules within the material, thus fully utilizing the active sites. When the specific surface area is too low, there are insufficient surface active sites, resulting in a low acetylene response value; when the specific surface area is too high, it is usually accompanied by further reduction in pore size, which may increase the diffusion resistance of gas molecules within the pores, prolonging the response and recovery time. Within the above range, good gas mass transfer efficiency can be maintained while ensuring sufficient specific surface area, which is beneficial for achieving rapid response and full recovery.

[0057] The molar ratio of Zn to Co in the porous zinc-cobalt composite oxide matrix is ​​70:30 to 99:1, preferably 92:8 to 97:3, for example, 97:3. The Zn to Co ratio directly affects the framework stability of the ZIF precursor, the content ratio of the two phases after calcination, and the heterojunction interface density. When the Zn / Co molar ratio is within the specified range, the ZIF precursor maintains good crystallinity and thermal stability. If the Zn content is too high and the Co3O4 content is too low, the number of heterojunctions is insufficient, the interface barrier modulation effect is weak, and the improvement in acetylene response is limited. If the Co content is too high and the Co3O4 phase content is excessive, the matrix resistivity decreases significantly, and may even dominate the conductivity, resulting in a low baseline resistance and reduced response value of the sensor. At the same time, excessive Co may destroy the ordered structure of the ZIF framework, affecting the specific surface area and pore integrity of the material after calcination.

[0058] In a second aspect, according to the method for preparing the composite oxide-based gas-sensitive material of the first aspect provided by the present invention, the method includes:

[0059] Step 1: Prepare bimetallic ZnCo-ZIF precursor;

[0060] Step 2: Introduce a noble metal precursor into the bimetallic organic framework precursor and perform a reduction treatment to obtain a noble metal modified composite material.

[0061] Step 3: Calcine the precious metal-modified composite material to obtain the gas-sensitive material.

[0062] The above methods will be described in detail below.

[0063] Step 1: Prepare bimetallic ZnCo-ZIF precursor.

[0064] In step 1, zinc salt and cobalt salt are dissolved in a first solvent to obtain a first mixture; imidazole ligands are dissolved in a second solvent to obtain a second mixture; the first mixture and the second mixture are mixed and reacted to obtain the bimetallic ZnCo-ZIF precursor.

[0065] The zinc salt is preferably one or more of zinc nitrate, zinc acetate, or zinc chloride. All three have good solubility and can fully dissociate Zn. 2+ It participates in coordination reactions. The nitrate ion of zinc nitrate does not participate in coordination, resulting in the cleanest reaction system with few byproducts, making it the preferred choice.

[0066] The cobalt salt is preferably one or more of cobalt nitrate, cobalt acetate, or cobalt chloride. These three cobalt salts have similar solubility and coordination behavior to the zinc salt, and can be co-soluble with the zinc salt in the first solvent in any proportion, ensuring Co concentration during the ZIF co-precipitation process. 2+ Able to uniformly replace Zn2+ Entering the framework node. The anions of the three cobalt salts do not participate in framework coordination and can be completely removed by washing, avoiding the adverse interference of residual impurities on the conductivity of the semiconductor gas-sensitive material.

[0067] The imidazole ligand is preferably 2-methylimidazolium. The two nitrogen atoms on the imidazole ring of the 2-methylimidazolium can react with Zn. 2+ / Co 2+ A stable tetrahedral coordination configuration was formed, constructing a dodecahedral ZIF crystal with a sodalite topology. The presence of methyl groups endowed the ZIF framework with certain hydrophobicity and thermal stability, allowing it to retain its dodecahedral morphology and porous structure even after calcination in air to remove organic components.

[0068] The first solvent is preferably N,N-dimethylformamide (DMF), and the second solvent is preferably methanol. DMF has excellent solubility for zinc and cobalt salts, and its weak basicity facilitates deprotonation, promoting the coordination reaction between imidazole ligands and metal ions. Methanol, as an auxiliary solvent, is used to dissolve 2-methylimidazole and, by adjusting the polarity and supersaturation of the reaction system, controls the nucleation and growth rate of ZIF crystals. The combined use of the two solvents ensures sufficient dissolution of the metal ions and ligands while avoiding uneven crystal size caused by excessively rapid nucleation in a single step.

[0069] The molar ratio of Zn in the zinc salt to Co in the cobalt salt is 70:30 to 99:1, preferably 92:8 to 97:3, for example, 97:3. Zn is the source of the main matrix phase ZnO, and Co is the source of the second phase Co3O4. When the Zn / Co ratio is within the above range, the Zn in the precursor framework... 2+ and Co 2+ It exhibits a uniform atomic-level distribution. After calcination, the two phases of ZnO and Co3O4 are uniformly intercalated at the nanoscale, forming a high-density pn heterojunction interface, which effectively amplifies the resistance change caused by acetylene adsorption.

[0070] The concentrations of the zinc and cobalt salts in the first solvent are 0.042–0.25 mmol / mL, preferably 0.1–0.15 mmol / mL. If the concentration is too low, the number of crystal nuclei formed is small, resulting in a low precursor yield; if the concentration is too high, the system is oversaturated, leading to rapid and abundant formation of ZIF crystal nuclei, resulting in excessively small crystal size and uneven particle size distribution, which in turn affects the morphological regularity of the oxide particles after calcination.

[0071] The concentration of the imidazole ligand in the second solvent is 0.25~4.0 mmol / mL, preferably 1~1.5 mmol / mL. If the concentration is too low, the amount of ligand is insufficient to completely coordinate all metal ions, resulting in a low precursor yield; if the concentration is too high, the ligand may not be completely dissolved, and the excess of ligand after mixing with the salt solution will lead to an excessive amount of free ligand in the reaction system, which will adsorb onto the ZIF crystal surface and inhibit further growth.

[0072] The sum of the amounts of zinc and cobalt salts used, in molar ratio to the imidazole ligands, is (4-6):1, for example, 4:1. In this invention, the ligand / metal molar ratio is higher than the theoretical value, ensuring sufficient coordination of metal ions and improving precursor yield. Excess ligands are effectively removed by washing after the reaction and will not remain in the ZIF framework. If the ligand / metal ratio is too low, coordination is insufficient, resulting in low precursor yield and potential uncoordinated metal ion defects in the framework, leading to impure oxide crystal phases after calcination. If the ligand / metal ratio is too high, the excess ligands act as inhibitors in the system, suppressing ZIF nuclei formation and growth on one hand, and increasing the difficulty of washing and removal on the other.

[0073] The mixing reaction time is 12-36 hours, preferably 24-36 hours. ZIF crystal growth is a coordination self-assembly process, requiring sufficient time for metal ions and ligands to fully diffuse, collide, and form a complete framework structure. If the reaction time is too short, crystal growth is incomplete, the precursor crystallinity is low, coordination defects exist in the framework, and the pore structure of the derived oxide may collapse or be incomplete after calcination, resulting in a decrease in specific surface area. If the reaction time is too long, the crystal size is too large, the intergranular packing pores decrease, and prolonged growth may lead to secondary nucleation and aggregation between crystals, which is detrimental to subsequent noble metal loading.

[0074] The mixing reaction temperature can be at room temperature, typically 25~35℃, for example, 30℃. This temperature range does not require special temperature control equipment, making operation simple, energy consumption low, and easy to scale up for production, which highly aligns with the process simplification requirements of industrial preparation.

[0075] Preferably, after the reaction is completed, the bimetallic organic framework precursor is obtained by centrifugation and drying.

[0076] During washing, methanol is preferred as the washing solvent to effectively remove residual ligands and solvent molecules adhering to the surface and pores of ZIF crystals. At the same time, methanol has low surface tension and boiling point, and is easily volatilized and removed during subsequent drying, so as not to form difficult-to-remove residues in the ZIF pores.

[0077] The drying process is preferably carried out at 60~100℃, for example 80℃, to remove methanol and moisture adsorbed in the ZIF channels, while keeping the temperature below the thermal decomposition temperature of the ZIF framework to ensure that the crystal structure and channel integrity of the precursor are not damaged.

[0078] Step 2: Introduce a noble metal precursor into the bimetallic organic framework precursor and perform a reduction treatment to obtain a noble metal-modified composite material.

[0079] In step 2, noble metals are introduced into the ZIF precursor stage and then reduced in a liquid phase. Compared to the traditional method of first calcining ZIF into oxides and then loading noble metals onto the oxide surface via impregnation or deposition precipitation, the precursor stage introduction and liquid phase reduction of this invention have the following significant advantages: First, the ZIF precursor has a regular microporous channel and cavity structure. Noble metal precursor molecules diffuse into the pores of ZIF and are spatially confined by the pores. During subsequent reduction and calcination, they are effectively restricted within the nanoscale space of the oxide derived from the ZIF framework, thereby inhibiting the aggregation and growth of noble metal particles; Second, Zn in the ZIF framework... The uniform distribution of / Co nodes provides abundant anchoring sites for noble metals. Noble metal precursors can be uniformly distributed on the ZIF surface and within the pores through electrostatic adsorption or weak coordination, forming highly dispersed noble metal nanoparticles after reduction. In addition, the noble metals are in close contact with the precursors of the matrix material during the ZIF stage. After calcination, a stable and tight metal-oxide interface is formed between the noble metals and ZnO / Co3O4, ensuring the efficient performance of electronic sensitization and catalytic spillover effects, without the problems of poor contact between Pt particles and oxide surfaces and poor interface consistency that occur in post-modification routes.

[0080] In step 2, the bimetallic ZnCo-ZIF precursor is dispersed in water and contacted with the aqueous solution of the noble metal precursor, so that the noble metal precursor is adsorbed on the surface and / or in the pores of the bimetallic ZnCo-ZIF precursor. Then, a reducing agent aqueous solution is added for reduction treatment to obtain the noble metal modified composite material.

[0081] The concentration of the bimetallic ZnCo-ZIF precursor in water is 0.01~0.12 g / mL, preferably 0.02~0.04 g / mL, for example 0.03 g / mL. At this concentration, the bimetallic ZnCo-ZIF precursor forms a suspension in water, ensuring sufficient dispersion of ZIF particles and providing ample liquid-phase contact opportunities for the adsorption of the noble metal precursor. If the amount of ZIF is too small or the water volume is too large, the collision probability between the noble metal precursor and the ZIF surface decreases, resulting in a large amount of noble metal precursor remaining free in the solution, wasting the noble metal, and reducing the loading efficiency. If the amount of ZIF is too large or the water volume is too small, the slurry becomes too thick, leading to ZIF particle agglomeration and uneven dispersion. The noble metal precursor may be over-adsorbed in localized areas, resulting in uneven distribution of the noble metal and agglomeration of the reduced particles.

[0082] The noble metal precursor is preferably one or more of chloroplatinic acid, chloroplatinate, or chloroplatinite. The chloroplatinic acid, chloroplatinate, or chloroplatinite all exhibit good solubility and stability in water, and can fully dissociate to release [PtCl6]. 2- Or [PtCl4] 2- Complex anions. The aforementioned complex anions carry a negative charge in solution, while Zn in the ZIF framework... 2+ / Co 2+ The nodes, in polar solvents, carry a certain positive charge or exhibit Lewis acidity on their surface, and there is an electrostatic attraction between the two, which facilitates the spontaneous adsorption of Pt precursor anions onto the ZIF surface and the inner walls of the pores. Simultaneously, the anionic ligands of the aforementioned Pt precursor are easily removed during subsequent reduction and washing processes.

[0083] The concentration of the noble metal precursor in water is 1-20 mg / mL, preferably 3-6 mg / mL, for example 5 mg / mL. If the concentration of the noble metal precursor is too low, the amount of noble metal introduced in the same volume is insufficient, resulting in too few noble metal catalytic active sites in the final material, an insignificant spillover effect, and limited promotion of the acetylene response. If the concentration of the noble metal precursor is too high, the solution is close to saturation, and the noble metal precursor may be rapidly over-adsorbed in local areas when mixed with the ZIF suspension. After reduction, the noble metal particles are prone to agglomeration and growth, reducing the utilization rate of noble metal atoms.

[0084] The mass ratio of the bimetallic ZnCo-ZIF precursor to the noble metal precursor is 6:1 to 200:1, preferably 20:1 to 100:1, for example, 60:1. In other words, the noble metal loading is 0.17 to 16.7 wt%, preferably 1 to 5 wt%, for example, 1.64 wt%. Within this range, the noble metal can be loaded onto the ZIF surface and pore walls in the form of highly dispersed nanoparticles, ensuring a sufficient number of catalytic active sites while avoiding pore blockage and particle agglomeration caused by excessive noble metal.

[0085] The reducing agent is preferably one or more of sodium borohydride, ascorbic acid, or hydrazine hydrate. The role of the reducing agent is to remove the Pt precursor (Pt) adsorbed on the ZIF surface. 4+ or Pt 2+ Sodium borohydride is reduced to metallic Pt nanoparticles. It has a strong reducing ability, rapidly reducing the Pt precursor to metallic Pt at room temperature. The reaction conditions are mild and the byproducts are easily removed, making it the preferred reducing agent in this invention.

[0086] The reducing agent has a concentration of 0.1~5 mg / mL in water, preferably 0.4~0.6 mg / mL, for example 0.5 mg / mL. This concentration range ensures the complete dissolution and stable existence of the reducing agent in water. If the reducing agent concentration is too low, the reducing ability is insufficient, the precursor conversion rate is low, and some noble metal species still exist in the oxidized state, affecting the catalytic activity; if the reducing agent concentration is too high, the reduction reaction is too violent, and noble metal crystal nuclei form rapidly and in large quantities and agglomerate, resulting in larger noble metal particle sizes and weakening the nanocatalytic effect.

[0087] The molar ratio of the reducing agent to the noble metal precursor is (4~8):1, preferably (4~5):1, for example, 4.4:1. Specifically, the molar ratio of the reducing agent to the noble metal precursor should ensure that the noble metal precursor is fully reduced to the metallic state. Taking the reduction of chloroplatinic acid with sodium borohydride as an example, the reduction reaction is: NaBH4 + H2PtCl6 + 3H2O → Pt↓ + NaCl + 5HCl + H3BO3 + 2H2↑. Theoretically, 1 mol of H2PtCl6 requires 1 mol of NaBH4. In this invention, the reducing agent is in excess relative to the noble metal precursor to ensure that the noble metal precursor is completely reduced to the metallic state, avoiding the reduction of catalytic activity due to the noble metal remaining in the oxidized state due to insufficient reduction. At the same time, the hydrogen gas generated by the decomposition of the excess reducing agent during the reaction has a stirring and auxiliary dispersing effect, which is beneficial to the uniform nucleation of noble metal nanoparticles and the maintenance of fine particle size. However, if the amount of reducing agent is too large, the excess reducing agent will remain in the system, which will increase the difficulty of washing and removal. Moreover, in a strong reducing environment, the noble metal crystal nuclei will be generated too quickly and in too large a number, which will easily lead to agglomeration and growth.

[0088] After the reaction is complete, the composite material modified with noble metals is obtained by separation, washing and drying.

[0089] The separation operation is preferably centrifugation, and washing is preferably performed 2-3 times with deionized water to remove unreacted noble metal precursors and residual reducing agents. Drying is preferably carried out at 60-80°C to remove moisture while preventing the migration and aggregation of noble metal nanoparticles during the drying process.

[0090] In a preferred embodiment, step 2 includes:

[0091] Step 2-1: Disperse the bimetallic ZnCo-ZIF precursor in water, sonicate and stir to obtain a bimetallic precursor suspension;

[0092] Step 2-2: Add the aqueous solution of the noble metal precursor to the bimetallic precursor suspension dropwise to obtain a composite material adsorbed with the noble metal precursor.

[0093] Steps 2-3: Add the reducing agent aqueous solution to the composite material adsorbed with the noble metal precursor to obtain the noble metal modified composite material.

[0094] In step 2-1, the cavitation effect and shear force generated by ultrasound effectively break down the soft agglomerates formed by ZIF particles during the drying process, allowing the ZIF crystals to be uniformly suspended in water in a monodisperse state, forming a stable suspension. This suspension ensures that the subsequently added noble metal precursor can fully contact each ZIF particle, providing the necessary conditions for the uniform adsorption of the noble metal precursor.

[0095] Preferably, the stirring rate is 600~1200 rpm, more preferably 800~1000 rpm, for example 800 rpm; the time is 5~20 min, more preferably 10~15 min, for example 10 min. These parameters ensure that the bimetallic ZnCo-ZIF precursor is fully dispersed.

[0096] In step 2-2, a dropwise addition method is used, with a drop rate of 0.5~1.5 mL / min, to control the contact rate between the noble metal precursor and the ZIF particles. Under the dropwise addition conditions, the noble metal precursor is added dropwise into the suspension, and the concentration of free noble metal precursor in the system remains at a low level. The adsorption sites on the ZIF surface and the inner wall of the pores can fully capture the noble metal precursor, achieving uniform adsorption.

[0097] In step 2-2, the stirring rate is kept constant during the dropwise addition. After the dropwise addition is complete, continue the reaction for 30-120 minutes, preferably 60 minutes, to allow the noble metal precursor to fully diffuse into the ZIF channels and reach adsorption equilibrium. If the stirring time is too short, the noble metal precursor will not have fully diffused into the ZIF channels, and a large amount of noble metal will only be adsorbed on the outer surface of the ZIF; if the stirring time is too long, adsorption has already reached equilibrium, and extending the time will not increase the adsorption amount and will reduce the preparation efficiency.

[0098] In steps 2-3, the addition of the reducing agent aqueous solution causes the Pt precursor adsorbed on the ZIF surface and the inner wall of the pores to be reduced in situ to metallic Pt nanoparticles. The added reducing agent aqueous solution is preferably prepared in an ice-water bath; and the stirring rate is maintained constant until the reaction is complete.

[0099] In steps 2-3, the reaction time is preferably 10-60 min, more preferably 30-40 min, for example 30 min. Within this time, the reduction reaction can proceed fully, the noble metal precursor is completely converted into the metallic state, and at the same time, the noble metal nanoparticles are generated in situ on the ZIF surface and the inner wall of the pores, maintaining a fine particle size due to the spatial confinement effect of the ZIF pores.

[0100] After the reduction reaction is completed, the composite material modified with noble metals is obtained by separation, washing and drying.

[0101] Step 3: Calcine the precious metal-modified composite material to obtain the gas-sensitive material.

[0102] In step 3, the organic ligand framework in the noble metal-modified composite material is transformed in situ into a porous zinc-cobalt composite oxide matrix through air calcination, while simultaneously allowing the noble metal nanoparticles to be stably loaded onto the surface and / or inner walls of the pores of the matrix. During the heating process in an air atmosphere, the organic ligands in the ZIF framework begin to decompose and oxidize above 350°C, releasing CO2, H2O, and nitrogen-containing gases, Zn 2+ and Co 2+ It then combines with oxygen in the air, transforming into ZnO and Co3O4 crystalline phases, respectively. As the temperature further increases, the organic components are completely removed, and the periodic pore structure of the ZIF framework is preserved and transformed into a porous oxide morphology, forming a composite oxide matrix with high specific surface area and abundant pore structure. At the same time, the metallic noble metal nanoparticles generated in step 2 are stably anchored on the surface and inner walls of the pores of the oxide matrix during calcination, forming a noble metal-oxide interface.

[0103] The calcination is carried out in an air atmosphere, with a calcination temperature of 400~500℃, a calcination time of 1~5h, and a heating rate of 1~5℃ / min.

[0104] Calcination temperature is a key parameter determining the final oxide product's crystal phase, pore structure, and noble metal dispersion state. Within the specified temperature range, ZIF organic ligands can be completely decomposed and removed, while ZnO and Co3O4 crystal phases fully crystallize, yielding a pure bicrystalline composite oxide. If the calcination temperature is too low, the organic ligands decompose incompletely, and residual carbonaceous species may cover the oxide and noble metal nanoparticle surfaces, occupying active sites and hindering the adsorption of target gas molecules. Simultaneously, the conversion of the ZIF framework to the oxide is insufficient, resulting in low ZnO / Co3O4 crystallinity and incomplete heterojunction interface formation. If the calcination temperature is too high, on the one hand, oxide grains grow excessively, the ZIF-derived porous structure sintersulates and collapses, the specific surface area decreases significantly, and gas molecule diffusion channels are reduced; on the other hand, noble metal nanoparticles tend to aggregate and grow at high temperatures, reducing the number of noble metal-oxide interfaces and weakening catalytic spillover effects and electron sensitization. Furthermore, excessively high calcination temperatures may cause solid-state reactions between ZnO and Co3O4 to generate impurity phases such as ZnCo2O4, disrupting the pn heterostructure.

[0105] Within the aforementioned calcination time range, the organic ligands in the ZIF framework can be fully oxidized and decomposed, the metal ions are completely transformed into oxide crystalline phases, and the interfacial bonding between the noble metal nanoparticles and the matrix tends to stabilize. If the calcination time is too short, the organic ligands will not decompose completely, residual carbonaceous species will not be thoroughly removed, and Zn... 2+ and Co2+ The conversion to oxides is incomplete, resulting in low crystallinity. If the calcination time is too long, the oxide grains continue to grow, the pore structure collapses further, the specific surface area decreases, and prolonged exposure of noble metal nanoparticles to high temperatures may lead to increased agglomeration.

[0106] A slower heating rate facilitates the gradual decomposition of organic ligands and uniform heat transfer, preventing drastic collapse of the ZIF framework structure and abnormal agglomeration of noble metal particles due to localized overheating. If the heating rate is too fast, the temperature difference between the interior and surface of the ZIF particles increases, and the rapid decomposition of organic ligands can lead to the instantaneous release of large amounts of gas, potentially damaging the material's pore structure. Simultaneously, localized overheating may cause agglomeration of noble metal nanoparticles. Conversely, if the heating rate is too slow, prolonged heating can result in excessive grain growth.

[0107] After the above-mentioned air calcination treatment, the organic ligands are completely removed, forming a porous zinc-cobalt composite oxide matrix with a multi-level pore structure. The ZnO and Co3O4 phases are uniformly intercalated at the nanoscale to form a pn heterojunction, and the noble metal nanoparticles are stably loaded on the matrix in a highly dispersed state, thus obtaining the gas-sensitive material.

[0108] Thirdly, the application of the composite oxide matrix gas sensitive material according to the first aspect or the composite oxide matrix gas sensitive material prepared according to the method of the second aspect, provided by the present invention, in sensors.

[0109] Fourthly, according to the present invention, an acetylene sensor is provided, the sensor comprising:

[0110] Insulating substrate 2, which is configured to provide mechanical support and electrical insulation;

[0111] Signal electrode 1 is disposed on the outer surface of the insulating substrate 2 and is configured to output the resistance signal of the sensitive layer 5.

[0112] Lead electrode 3, electrically connected to the signal electrode 1, is configured to transmit the resistance signal to the test circuit.

[0113] Heating element 4, which is disposed inside the insulating substrate 2, is configured to provide operating temperature for sensitive layer 5;

[0114] A sensitive layer 5, covering the outer surface of the insulating substrate 2 and the signal electrode 1, is configured to undergo a reversible resistance change upon contact with acetylene molecules, thereby enabling quantitative detection of acetylene gas. The sensitive layer 5 contains the composite oxide-based gas-sensitive material described in the first aspect.

[0115] The insulating substrate 2 is made of Al2O3 ceramic material and has a hollow tubular structure, serving as an Al2O3 ceramic tube. Al2O3 ceramic has extremely high resistivity, ensuring electrical isolation between the heating element 4 and the signal electrode 1. Simultaneously, Al2O3 ceramic has excellent thermal conductivity, efficiently and uniformly conducting the heat generated by the heating element 4 to the sensitive layer 5 on the outer surface of the tube, allowing the sensitive layer 5 to quickly reach and stabilize at its operating temperature. Al2O3 ceramic also possesses good thermal stability and chemical inertness, remaining undeformed or decomposed at the sensor's long-term operating temperature, and does not chemically react with the measured acetylene gas or oxygen and moisture in the test atmosphere, ensuring the long-term structural stability and service life of the sensor substrate.

[0116] The length of the insulating substrate 2 is 4.0~4.5mm. If the length is too short, the area available for coating the sensitive layer 5 on the outer surface of the insulating substrate 2 is insufficient, the loading of gas sensitive material is limited, resulting in the resistance value of the sensitive layer 5 being too high or unstable, affecting the reliability of the signal output; if the length is too long, the overall size of the sensor increases, which is not conducive to miniaturization and integration, and the heat capacity increases, the time required for the heating element 4 to reach thermal equilibrium is prolonged, and the power consumption increases.

[0117] The outer diameter of the insulating substrate 2 is 1.1~1.35mm. If the outer diameter is too small, the mechanical strength is insufficient and it is easy to break, and the coating area of ​​the sensitive layer 5 is limited; if the outer diameter is too large, the heat capacity and size increase, the heating power consumption increases, and the response speed decreases.

[0118] The wall thickness of the insulating substrate 2 is 0.2~0.35mm. If the wall thickness is too thin, the mechanical strength is insufficient, and it is easily damaged during the installation of the heating element 4 and the coating operation. In addition, the heat conduction path is too short, which may lead to uneven temperature distribution on the outer surface. If the wall thickness is too thick, the heat conduction path is longer, the thermal resistance is increased, and the efficiency of the heat from the heating element 4 reaching the outer surface sensitive layer 5 is reduced.

[0119] The signal electrode 1 is disposed on the outer surface of the insulating substrate 2, and adopts a ring electrode structure, preferably gold. Gold has excellent conductivity and extremely high chemical inertness, and is not easily oxidized or corroded in the sensor's operating temperature and test atmosphere. It can maintain stable electrical contact performance for a long time, and has long-term stability and repeatability of the sensor's resistance signal output.

[0120] The signal electrode 1 adopts a ring electrode structure, surrounding the outer surface of the insulating substrate 2. The ring structure significantly increases the effective contact area between the electrode and the sensitive layer 5, reduces the contact resistance, and helps to improve the signal-to-noise ratio.

[0121] Two signal electrodes 1 are respectively disposed at both ends of the outer surface of the insulating substrate 2. The two annular gold electrodes serve as two acquisition terminals for the resistance signal, connected to an external test circuit via lead electrodes 3 to measure the resistance value of the sensitive layer 5. The spacing between the two electrodes determines the effective resistance measurement length of the sensitive layer 5.

[0122] Furthermore, the spacing between the two signal electrodes 1 is 0.5~0.55mm. If the spacing is too small, the effective resistance measurement path between the two electrodes is too short, the resistance base value of the sensitive layer 5 is too low, and the absolute value of the resistance change is too small, which is not conducive to the accurate acquisition and amplification of weak signals by the test circuit; if the spacing is too large, the effective resistance measurement path is too long, which increases the input impedance requirements of the signal acquisition circuit.

[0123] The thickness of the signal electrode 1 is 1~5μm. If the thickness is too thin, the contact resistance increases and becomes unstable, affecting the reliability of signal acquisition; if the thickness is too thick, although the conductivity is better, it increases the amount of precious metal gold used, increasing the manufacturing cost, and the adhesion of the excessively thick electrode layer to the surface of the ceramic tube may decrease, posing a risk of peeling off during subsequent coating and heat treatment processes.

[0124] The width of the signal electrode 1 is 0.2~0.45mm. If the width is too small, the contact area between the signal electrode 1 and the sensitive layer 5 is insufficient, the contact resistance is large, and it is easily affected by local coating defects; if the width is too large, the effective distance between the two electrodes is reduced.

[0125] One end of the lead electrode 3 is fixed to the surface of the signal electrode 1, and the other end is a free end used to connect to an external test circuit. The two lead electrodes 3 are respectively connected to the two signal electrodes 1.

[0126] The lead electrode 3 is made of platinum wire. Platinum has excellent conductivity and extremely high chemical stability, which can ensure long-term low-loss and stable transmission of the resistance signal. At the same time, platinum wire has excellent ductility and solderability, which facilitates a firm electrical connection with the ring-shaped gold electrode 1. Furthermore, the contact potential difference between platinum and gold is extremely small, which is beneficial for obtaining a stable, low-noise resistance signal.

[0127] The platinum wire is preferably 0.045~0.055mm in diameter and 4~6mm in length. If the diameter is too small, the mechanical strength of the platinum wire is insufficient, making it prone to breakage during sensor use. Furthermore, its high resistance may generate significant line resistance and thermal noise during signal transmission, affecting signal acquisition accuracy. If the diameter is too large, excessive heat may be conducted away from the signal electrode 1 and the sensitive layer 5, resulting in a lower actual operating temperature or uneven temperature distribution in the sensitive layer 5. If the length is too short, a reliable connection with the external test circuit may not be possible. If the length is too long, it increases the resistance and inductance in the signal transmission path, potentially introducing additional noise interference.

[0128] The heating element 4 is inserted into the hollow channel inside the insulating substrate 2, and its two ends extend out of the two end faces of the insulating substrate 2 to form the heating element lead-out end 6.

[0129] The heating element 4 is made of nickel-chromium alloy, which facilitates predictable and repeatable heating power output by applying a stable DC voltage. Simultaneously, the nickel-chromium alloy possesses excellent high-temperature oxidation resistance, ensuring the long-term operational reliability and service life of the heating element 4.

[0130] The diameter of the heating element 4 is 0.03~0.06mm. If the diameter is too small, the mechanical strength is insufficient, and it is easy to curl, bend or even break. At the same time, the small cross-sectional area makes its resistance value too high, and the heat power generated under the same heating voltage is limited, making it difficult to heat the sensitive layer 5 to the required operating temperature. If the diameter is too large, the rigidity is increased, making it difficult to bend and insert. The increased cross-sectional area leads to a low resistance value, and the heating power is too high under normal DC voltage, which may cause the insulating substrate 2 and the sensitive layer 5 to overheat or even burn out.

[0131] The resistance of the heating element 4 is 28~35Ω. If the resistance is too low, the heating current will be too large and the power too high under the same voltage, which may cause the operating temperature of the sensitive layer 5 to be too high and accelerate the aging of the material, and also require a high current output capability of the power supply circuit; if the resistance is too high, the heating power will be insufficient under the same voltage, and the sensor response value will be too low.

[0132] The heating element 4 is partially spring-like and inserted inside the insulating substrate 2 to significantly increase the effective length within the limited internal space of the ceramic tube, thereby increasing the total resistance of the heating element 4. This allows the required heating power to be obtained at a lower heating voltage, reducing the requirements for the power supply. At the same time, the elastic tension of the spring helps to securely position the heating element 4 inside the insulating substrate 2, preventing axial movement during transportation and use.

[0133] The spring-like structure has a length of 2.5~3.5mm, an outer diameter of 0.5~0.8mm, and 10~20 turns. The length of the spring-like structure ensures a uniform temperature distribution along the axial direction of the sensitive layer, preventing the effective detection area from being shortened due to lower temperatures at both ends. Its outer diameter ensures efficient heat conduction to the outer surface of the sensitive layer 5. The number of turns ensures that the sensor can obtain sufficient power to heat the sensitive layer 5 to its operating temperature under conventional DC heating voltage. These three dimensional parameters together ensure that the heating element 4 forms a uniform heating body that matches the spatial position of the sensitive layer 5, enabling the sensitive layer 5 to obtain a stable and uniform operating temperature field, thus guaranteeing a high and stable gas-sensitive response from the sensor.

[0134] The heating element lead-out end 6 extends a certain length beyond both ends of the insulating substrate 2 to facilitate electrical connection with an external DC heating power supply. The two leads are spatially separated to avoid short circuits.

[0135] The sensitive layer is the core functional component of the sensor, and its material composition and structure directly determine the sensor's gas-sensitive response characteristics to acetylene. The gas-sensitive material described in the first aspect of the sensitive layer 5 endows it with excellent gas-sensitive performance: the pn heterojunction formed between ZnO and Co3O4 can adjust the depletion layer width, significantly amplifying the resistance change rate caused by acetylene adsorption; the porous structure facilitates the rapid diffusion and adsorption of acetylene molecules; and the noble metal nanoparticles, as highly efficient catalytic active centers, can reduce the activation energy of the acetylene oxidation reaction, further enhancing the sensor's sensitivity and selectivity.

[0136] The sensitive layer 5 is formed on the outer surface of the insulating substrate (2) by coating and completely covers the signal electrode 1, forming a tight electrical contact interface with the annular gold electrode 1. When acetylene molecules come into contact with the sensitive layer 5, the resistance value of the sensitive layer 5 undergoes a reversible change, which is then output to the external test circuit through the signal electrode 1 and the lead electrode 3, thereby realizing the quantitative detection of acetylene gas.

[0137] The thickness of the sensitive layer 5 is 20~50μm. If the thickness is too thin, the loading of gas-sensitive material is insufficient, and the absolute value of the resistance change caused by acetylene molecule adsorption is too small, resulting in a low response value. If the thickness is too thick, gas molecules need to diffuse a longer path to reach the bottom of the sensitive layer 5, increasing the mass transfer resistance and significantly prolonging the response time and recovery time. At the same time, an excessively thick sensitive layer 5 is prone to cracking or peeling due to volume shrinkage during drying and heat treatment, reducing the long-term stability and service life of the sensor.

[0138] In a preferred embodiment, the sensitive layer 5 is formed on the outer surface of the insulating substrate 2 and the signal electrode 1 by mixing the gas-sensitive material with an organic binder and grinding it into a slurry; coating the slurry on the outer surface of the insulating substrate 2 and the signal electrode 1; and then drying, calcining again, and aging.

[0139] The organic binder is preferably terpineol. Terpineol has a moderate viscosity, which facilitates uniform coating of the slurry into a film; and it decomposes completely during secondary calcination, leaving no carbonaceous impurities, thus ensuring the purity of the surface activity of the sensitive layer 5.

[0140] The ratio of the gas-sensitive material to the organic binder is 1 mg: 1~5 μL. This ratio gives the slurry suitable solid content and rheological properties, ensuring that the slurry has sufficient fluidity to cover the outer surface of the insulating substrate 2 and the microscopic uneven areas of the signal electrode 1, while also ensuring that the sensitive layer 5 has sufficient thickness and structural integrity after coating.

[0141] The secondary calcination temperature is 300~400℃, the heating rate is 1~5℃ / min, and the time is 1~5h. Within this parameter range, organic binders such as terpineol are completely oxidized and removed, leaving no carbonaceous impurities in the sensitive layer 5. This prevents carbonaceous species from covering the active sites on the surface of the sensitive material and reducing the gas-sensitive response. At the same time, this temperature is lower than the calcination temperature during preparation, so it will not significantly affect the crystal structure, porous morphology, and noble metal dispersion state of the gas-sensitive material, ensuring that the sensitive material retains its original gas-sensitive performance after coating and molding.

[0142] The aging treatment is performed at a temperature of 300-400℃ for 24-120 hours. The aging treatment is carried out after the second calcination, and its purpose is to allow the sensitive layer 5 to undergo a sufficient structural relaxation and stabilization process at a constant operating temperature, eliminating micro-stresses and defects that may be introduced during the coating and second calcination processes.

[0143] Furthermore, after the aging process, a heating element 4 is inserted into the hollow channel inside the insulating substrate 2 with the sensitive layer 5, so that the heating element 4 is placed in the middle with a spring-like structure, and its two ends extend straight out from both ends of the insulating substrate 2 to form heating wire lead-out ends 6, which are used to connect a DC heating voltage later. A lead electrode 3 is led out from the signal electrode 1 to obtain a Pt-modified ZnO / Co3O4-based acetylene sensor.

[0144] Example

[0145] The present invention is further described below through specific examples; however, these examples are merely exemplary and do not constitute any limitation on the scope of protection of the present invention.

[0146] Example 1

[0147] (1) Weigh 2.886 g of zinc nitrate hexahydrate and 0.087 g of cobalt nitrate hexahydrate to make the total amount of metal salt 10 mmol and the Zn:Co molar ratio 97:3. Dissolve both in 75 mL of N,N-dimethylformamide. Separately weigh 3.285 g of 2-methylimidazole and dissolve it in 37.5 mL of methanol. After sonicating the two precursor solutions separately for 5 min, mix them and continue sonicating for 5 min. Then seal with aluminum foil and react at 30 °C for 24 h. After the reaction is complete, collect the product by centrifugation, wash three times with methanol, and dry at 80 °C to obtain the bimetallic ZnCo-ZIF precursor.

[0148] (2) Weigh 300 mg of the above bimetallic ZnCo-ZIF precursor, add it to 10 mL of deionized water, sonicate for 10 min, and then stir at 800 rpm for 10 min to fully disperse the powder. Under continuous stirring, add 1 mL of potassium chloroplatinate aqueous solution with a concentration of 5 mg / mL dropwise at a rate of 1 mL / min, and stir at room temperature for 60 min to allow the Pt precursor to adsorb onto the surface of the bimetallic ZnCo-ZIF precursor. Then add 4 mL of freshly prepared 0.5 mg / mL sodium borohydride aqueous solution in an ice-water bath, and maintain stirring at 800 rpm for 30 min. After the reaction is complete, collect the product by centrifugation, wash twice with deionized water, and dry at 80 °C to obtain the Pt-modified ZnCo-ZIF composite material.

[0149] (3) The Pt-modified ZnCo-ZIF composite material was placed in a quartz boat and transferred to a tube furnace. Under an air atmosphere, the temperature was increased from 25°C to 450°C at a rate of 2°C / min and calcined for 3 hours. After calcination, it was naturally cooled to room temperature to obtain the gas-sensitive material, namely the Pt-modified ZnO / Co3O4 composite oxide acetylene-sensitive material.

[0150] Figure 2 Image (a) shows a scanning electron microscope image of the prepared gas-sensitive material. Figure 2 Image (b) shows a high-power scanning electron microscope image, which reveals that the material exhibits a dodecahedral structure and forms microspheres on its surface;

[0151] Figure 3 The high-angle annular dark-field scanning transmission electron microscope image and the elemental distribution diagram of Pt, Zn, Co, and O of the prepared gas-sensitive material are shown. It can be seen that the material has uniform size and uniform elemental distribution.

[0152] Figure 4 The X-ray diffraction pattern of the prepared gas-sensitive material is shown, revealing three phases: ZnO, Co3O4, and Pt. The characteristic diffraction peaks of each phase match their corresponding standard cards. The diameter of the Pt nanoparticles is calculated to be 4 nm using the Scherrer equation.

[0153] Figure 5 The N2 adsorption-desorption curves of the prepared gas-sensitive material are shown. It can be seen that the material exhibits a type IV adsorption isotherm and has a specific surface area of ​​24.08 m². 2 / g.

[0154] Figure 6 The pore size distribution of the prepared gas-sensitive material is shown. It can be seen that the mesopore range of the material is 2~50nm, with 31nm as the main pore size. At the same time, there is a hierarchical pore structure of micropores (<2nm) and macropores (>50nm).

[0155] Example 2

[0156] (1) Weigh 2.826 g of zinc nitrate hexahydrate and 0.146 g of cobalt nitrate hexahydrate to make the total amount of metal salt 10 mmol and the Zn:Co molar ratio 95:5. Dissolve both in 75 mL of N,N-dimethylformamide. Separately weigh 3.285 g of 2-methylimidazole and dissolve it in 37.5 mL of methanol. After sonicating the two precursor solutions separately for 5 min, mix them and continue sonicating for 5 min. Then seal with aluminum foil and react at 30 °C for 24 h. After the reaction is complete, collect the product by centrifugation, wash three times with methanol, and dry at 80 °C to obtain the bimetallic ZnCo-ZIF precursor.

[0157] (2) Weigh 300 mg of the above bimetallic ZnCo-ZIF precursor, add it to 10 mL of deionized water, sonicate for 10 min, and then stir at 800 rpm for 10 min to fully disperse the powder. Under continuous stirring, add 1 mL of potassium chloroplatinate aqueous solution with a concentration of 5 mg / mL dropwise at a rate of 0.5 mL / min, and stir at room temperature for 60 min to allow the Pt precursor to adsorb onto the surface of the bimetallic ZnCo-ZIF precursor. Then add 4 mL of freshly prepared 0.5 mg / mL sodium borohydride aqueous solution in an ice-water bath, and maintain stirring at 800 rpm for 30 min. After the reaction is complete, collect the product by centrifugation, wash twice with deionized water, and dry at 80 °C to obtain the Pt-modified ZnCo-ZIF composite material.

[0158] (3) The Pt-modified ZnCo-ZIF composite material was placed in a quartz boat and transferred to a tube furnace. Under an air atmosphere, the temperature was increased from 25°C to 450°C at a rate of 2°C / min and calcined for 3 hours. After calcination, it was naturally cooled to room temperature to obtain the gas-sensitive material, namely the Pt-modified ZnO / Co3O4 composite oxide acetylene-sensitive material.

[0159] Figure 7 Image (a) shows a scanning electron microscope image of the prepared gas-sensitive material. Figure 7 Image (b) shows a high-power scanning electron microscope image, which reveals that the material exhibits a dodecahedral structure and forms microspheres on its surface;

[0160] Figure 8 The high-angle annular dark-field scanning transmission electron microscope image and the elemental distribution diagram of Pt, Zn, Co, and O of the prepared gas-sensitive material are shown. It can be seen that the material has uniform size and uniform elemental distribution.

[0161] Figure 9 The X-ray diffraction pattern of the prepared gas-sensitive material is shown, revealing three phases: ZnO, Co3O4, and Pt. The characteristic diffraction peaks of each phase match their corresponding standard cards. The diameter of the Pt nanoparticles is calculated to be 4 nm using the Scherrer equation.

[0162] Figure 10 The N2 adsorption-desorption curves of the prepared gas-sensitive material are shown. It can be seen that the material exhibits a type IV adsorption isotherm and has a specific surface area of ​​15.61 m². 2 / g.

[0163] Figure 11 The pore size distribution of the prepared gas-sensitive material is shown. It can be seen that the mesopore range of the material is 2~50nm, with 23nm being the main pore size. At the same time, there is a hierarchical pore structure of micropores (<2nm) and macropores (>50nm).

[0164] Example 3

[0165] (1) Weigh 2.737 g of zinc nitrate hexahydrate and 0.233 g of cobalt nitrate hexahydrate to make the total amount of metal salt 10 mmol and the Zn:Co molar ratio 92:8. Dissolve both in 75 mL of N,N-dimethylformamide. Separately weigh 3.285 g of 2-methylimidazole and dissolve it in 37.5 mL of methanol. Sonicate the two precursor solutions separately for 5 min each, then mix them and sonicate for another 5 min. Seal the mixture with aluminum foil and react it at 30 °C for 24 h. After the reaction is complete, centrifuge to collect the product, wash it three times with methanol, and dry it at 80 °C to obtain the bimetallic ZnCo-ZIF precursor.

[0166] (2) Weigh 300 mg of the above bimetallic ZnCo-ZIF precursor, add it to 10 mL of deionized water, sonicate for 10 min, and then stir at 800 rpm for 10 min to fully disperse the powder. Under continuous stirring, add 1 mL of potassium chloroplatinate aqueous solution with a concentration of 5 mg / mL dropwise at a rate of 1.5 mL / min, and stir at room temperature for 60 min to allow the Pt precursor to adsorb onto the surface of the bimetallic ZnCo-ZIF precursor. Then add 4 mL of freshly prepared 0.5 mg / mL sodium borohydride aqueous solution in an ice-water bath, and maintain stirring at 800 rpm for 30 min. After the reaction is complete, collect the product by centrifugation, wash twice with deionized water, and dry at 80 °C to obtain the Pt-modified ZnCo-ZIF composite material.

[0167] (3) The Pt-modified ZnCo-ZIF composite material was placed in a quartz boat and transferred to a tube furnace. Under an air atmosphere, the temperature was increased from 25°C to 450°C at a rate of 2°C / min and calcined for 3 hours. After calcination, it was naturally cooled to room temperature to obtain the gas-sensitive material, namely the Pt-modified ZnO / Co3O4 composite oxide acetylene-sensitive material.

[0168] Figure 12 Image (a) shows a scanning electron microscope image of the prepared gas-sensitive material. Figure 12Image (b) shows a high-power scanning electron microscope image, which reveals that the material exhibits a dodecahedral structure and forms microspheres on its surface;

[0169] Figure 13 The high-angle annular dark-field scanning transmission electron microscope image and the elemental distribution diagram of Pt, Zn, Co, and O of the prepared gas-sensitive material are shown. It can be seen that the material has uniform size and uniform elemental distribution.

[0170] Figure 14 The X-ray diffraction pattern of the prepared gas-sensitive material is shown, revealing three phases: ZnO, Co3O4, and Pt. The characteristic diffraction peaks of each phase match their corresponding standard cards. The diameter of the Pt nanoparticles is calculated to be 4 nm using the Scherrer equation.

[0171] Figure 15 The N2 adsorption-desorption curves of the prepared gas-sensitive material are shown. It can be seen that the material exhibits a type IV adsorption isotherm and has a specific surface area of ​​23.31 m². 2 / g.

[0172] Figure 16 The pore size distribution of the prepared gas-sensitive material is shown. It can be seen that the mesopore range of the material is 2~50nm, with 23nm being the main pore size. At the same time, there is a hierarchical pore structure of micropores (<2nm) and macropores (>50nm).

[0173] Comparing Examples 1-3, it can be seen that the Zn / Co molar ratio of Example 1 is 97:3, which not only forms a sufficient pn heterojunction but also avoids excessive Co3O4 from reducing the baseline resistance, resulting in a high sensitivity response to acetylene. In addition, the average mesopore diameter reaches 31 nm, which is larger than that of Examples 2-3, making it more conducive to the rapid diffusion and adsorption of acetylene molecules, enabling rapid detection of acetylene, and thus obtaining the best gas sensing performance.

[0174] Example 4

[0175] The gas-sensitive material prepared in Example 1 was mixed with terpineol at a ratio of 1 mg: 2 μL and thoroughly ground in an agate mortar to form a uniform slurry. An Al2O3 ceramic tube with an annular gold electrode was ultrasonically cleaned in deionized water and ethanol for 10 min, then dried at room temperature. The slurry was drop-coated onto the outer surface of the pretreated Al2O3 ceramic tube, ensuring complete coverage of the outer surface and the two annular gold electrodes. The coated ceramic tube was dried on a 100°C hot plate for 12 h, then transferred to a tube furnace and calcined in air at a rate of 2°C / min from room temperature (25°C) to 350°C for 3 h; subsequently, it was aged at 300°C for 72 h. After aging, the annular gold electrode was connected to a platinum wire lead, and a nickel-chromium heating wire was threaded inside the Al2O3 ceramic tube, with both ends extending out of the tube to form heating wire leads; the tube was then welded and encapsulated to obtain the acetylene sensor.

[0176] The gas-sensing performance of the sensor prepared in Example 4 was tested. The test system included a gas path, a heating circuit, and a test circuit. During the test, the gas flow rate was adjusted by a mass flow controller, with the total gas flow rate maintained at 500 sccm and the oxygen flow rate maintained at 105 sccm, so that the oxygen volume fraction in the mixed gas was 21%. The background gas for the acetylene standard gas was nitrogen, which was adjusted to the required concentration by the mass flow controller.

[0177] The sensor's operating temperature is controlled by applying a DC heating voltage to the nichrome heating wire. The response value is Ra / Rg, which represents the sensor's resistance Ra in air and Rg in an acetylene atmosphere.

[0178] Figure 17 Figure (a) shows the response curve of the sensor to 100 ppm acetylene as a function of temperature. It can be seen that the sensor's response to 100 ppm acetylene first increases and then decreases as the operating temperature increases, reaching a better state near 240℃.

[0179] Figure 17 Figure (b) shows the dynamic response curve of the sensor to the concentration gradient of 20-160 ppm acetylene at 240 °C, indicating that the sensor's response value to 20-160 ppm acetylene increases from 3.49 to 10.81 as the concentration increases at 240 °C.

[0180] Figure 17 Figure (c) shows the linear response fitting curve of the sensor in the range of 20–80 ppm, indicating that the response value has a good linear relationship with the acetylene concentration in the range of 20–80 ppm. The linear fitting equation is y = 0.068x + 2.147, and the correlation coefficient R is 1 / 2. 2 The value was 0.994, and the theoretical detection limit was 0.50 ppm.

[0181] Figure 17 Figure (d) shows the response / recovery time curves of the sensor at different acetylene concentrations, indicating that in the acetylene concentration range of 20~160ppm, the sensor's response time is shortened from 76s to 34s, and the recovery time is increased from 214s to 293s.

[0182] Figure 17 Figure (e) shows the response curve of the sensor to 100 ppm acetylene in 5 cycles. The coefficient of variation of the response value is 2.87%, which indicates that the sensor has good repeatability.

[0183] Figure 17 Figure (f) shows the selective response of the sensor to acetylene and common interfering gases, indicating that the sensor prepared in Example 4 has a significantly higher response to acetylene than to the interfering gases, demonstrating that it has good selectivity for acetylene.

[0184] The present invention has been described in detail above with reference to preferred embodiments and exemplary examples. However, it should be noted that these specific embodiments are merely illustrative explanations of the invention and do not constitute any limitation on the scope of protection of the invention. Various improvements, equivalent substitutions, modifications, or arbitrary combinations can be made to the technical content and embodiments of the present invention without departing from the spirit and scope of protection of the invention, and all such improvements fall within the scope of protection of the present invention. The scope of protection of the present invention is defined by the appended claims.

Claims

1. A composite oxide-based gas-sensitive material, characterized in that, The gas-sensitive material comprises a porous zinc-cobalt composite oxide matrix and noble metal nanoparticles; the noble metal nanoparticles are loaded on the porous zinc-cobalt composite oxide matrix.

2. The gas-sensitive material according to claim 1, characterized in that, The porous zinc-cobalt composite oxide matrix comprises ZnO and Co3O4 crystal phases.

3. The gas-sensitive material according to claim 1, characterized in that, The porous zinc-cobalt composite oxide matrix is ​​composed of dodecahedral particles.

4. The gas-sensitive material according to claim 1, characterized in that, The noble metal nanoparticles are platinum nanoparticles.

5. The gas-sensitive material according to claim 1, characterized in that, In the porous zinc-cobalt composite oxide matrix, the molar ratio of Zn to Co is 70:30 to 99:

1.

6. A method for preparing the composite oxide-based gas-sensitive material according to any one of claims 1 to 5, characterized in that, The method includes: Step 1: Prepare a bimetallic organic framework precursor containing zinc and cobalt; Step 2: Introduce a noble metal precursor into the bimetallic organic framework precursor and perform a reduction treatment to obtain a noble metal modified composite material. Step 3: Calcine the precious metal-modified composite material to obtain the gas-sensitive material.

7. The method according to claim 6, characterized in that, In step 1, zinc salt and cobalt salt are dissolved in a first solvent to obtain a first mixture; imidazole ligands are dissolved in a second solvent to obtain a second mixture; the first mixture and the second mixture are mixed and reacted to obtain the bimetallic ZnCo-ZIF precursor.

8. The application of the composite oxide matrix gas sensitive material according to any one of claims 1 to 5 or the composite oxide matrix gas sensitive material prepared by the method according to any one of claims 6 to 7 in the field of sensors.

9. An acetylene sensor, characterized in that, The sensor includes a sensitive layer (5) containing the composite oxide matrix gas sensitive material as described in any one of claims 1 to 5.

10. The sensor according to claim 9, characterized in that, The sensor also includes: Insulating substrate (2), which is configured to provide mechanical support and electrical insulation; The signal electrode (1) is disposed on the outer surface of the insulating substrate (2) and is configured to output the resistance signal of the sensitive layer (5); The lead electrode (3) is electrically connected to the signal electrode (1) and is configured to transmit the resistance signal to the test circuit. The heating element (4) is disposed inside the insulating substrate (2) and is configured to provide operating temperature for the sensitive layer (5).